2021
DOI: 10.1039/d1ra06340e
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron photofragment coincidence spectroscopy of carboxylates

Abstract: Photoelectron photofragment coincidence spectroscopy studies of a range of carboxylate anions are reviewed, revealing details of the decarboxylation dynamics of carboxyl radicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In addition, there are two bound anionic asymptotes. Photodetachment experiments that measure electron kinetic energy in coincidence with the kinetic energy release of the neutral molecules, such as those developed by Continetti, provide a direct measure of the repulsion between the two neutral molecules prepared by detachment of the anion. , …”
Section: [O2–m] – Complex Anionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are two bound anionic asymptotes. Photodetachment experiments that measure electron kinetic energy in coincidence with the kinetic energy release of the neutral molecules, such as those developed by Continetti, provide a direct measure of the repulsion between the two neutral molecules prepared by detachment of the anion. , …”
Section: [O2–m] – Complex Anionsmentioning
confidence: 99%
“…Photodetachment experiments that measure electron kinetic energy in coincidence with the kinetic energy release of the neutral molecules, such as those developed by Continetti, provide a direct measure of the repulsion between the two neutral molecules prepared by detachment of the anion. [61][62][63]95 Taken a step further, there can be instances of partial covalent bond formation between an anion and a neutral that has a negative EA (cannot bind an electron as an isolated molecule) but with a corresponding noncovalently interacting neutral van der Waals complex. Both cases will be touched on here, in the context of the O 2 − primary anion, with its modest EA of 0.448 eV (e.g., molecule "A" in Figure 6).…”
Section: Complexes Formed Between Omentioning
confidence: 99%
“…Lineberger and co-workers demonstrated this using PE spectroscopy on the C 6 H 5 – phenide anion, determining the EA of ·C 6 H 5 to be 1.096 eV. Anion PE spectroscopy has been an important tool used to explore the electronic structures of organic radical species, with several elegant examples included in refs . Of course, the phenyl radical in particular is an important intermediate in many chemical processes and has been the subject of numerous spectroscopic investigations, several of which are also included in refs .…”
Section: Introductionmentioning
confidence: 99%
“…47 Another possible explanation for the observed decay dynamics is the depopulation of the Phe˙ radical by fragmentation, for example, via the decarboxylation pathway that was previously observed from nanosecond laser and microsecond flash photolysis studies of the Phe − anion in alkaline medium. 7–9 While our experimental data does not provide any direct evidence that rules out the possibility of decarboxylation occurring in the phenylalanine radical – indeed this has been shown in studies of gas-phase photodetached carboxylate anions to be the dominant dissociation pathway 48,49 – we note that both anion photoelectron spectroscopy and ab initio calculations have shown that microhydrated carboxyl radicals are stable with respect to decarboxylation. 50,51 Consistent with previous studies of microhydrated carboxyl radicals, results from our DFT calculations suggest that decarboxylation does not occur on the picosecond timescale (see below).…”
Section: Resultsmentioning
confidence: 53%
“…These modes can then be used to track the vibrational relaxation dynamics of the Phe˙ radical from the Franck–Condon region to its equilibrium geometry. In the present work, rapid dephasing promoted by the strong anharmonic coupling between the C1–C2 elongation and, for example, the CO 2 bend 49 suppresses the observation of vibrational wave packet dynamics along these modes. We note that the strong quenching of vibrational coherences involving vibrational modes that are strongly coupled to the reaction coordinate has previously been observed in intersystem crossing, 65 internal conversion, 66 and excited-state intramolecular proton transfer.…”
Section: Resultsmentioning
confidence: 54%